Foucault and Shakespeare: Ceremony, Theatre, Politics. (September 2017) - Elden, Stuart
Abstract: Foucault only refers to Shakespeare in a few places in his work. He is intrigued by the figures of madness that appear in King Lear, Hamlet, and Macbeth . He occasionally notes the overthrow of one monarch by another, such as in Richard II or Richard III, arguing that "a part of Shakespeare's historical drama really is the drama of the coup d'État ." For Foucault, the first are illustrations of the conflict between the individual and the mechanisms of discipline. The second are, however, less interesting than moments when the sovereign is replaced, not with another sovereign, but with a different, more anonymous, form of power. Yet, in his 1976 Collège de France course, Society Must Be Defended, where he treats the theme at most length, he intriguingly suggests that Shakespearean historical tragedy is "at least in terms of one of its axes, a sort of ceremony, or a rememorialization of the problems of public right." Foucault was long fascinated by the theatre, and especially its relation to political ceremony. Drawing especially on his 1972 lectures in Paris and a related presentation in Minnesota, this paper asks how we might understand the relation between ceremony, theatre, and politics in Foucault and Shakespeare. Many of Shakespeare's plays, both histories and tragedies, thus demonstrate the importance of ritual and ceremony, a political theatre. Examining the disrupted ceremony of King Lear, the repeated ceremony of King John, the denial of ritual in Coriolanus, and the parody of the ceremonial in Henry IV, Part One opens up a range of historical, theoretical, and political questions.